Case Report: Severe Hypocalcemic Episodes Due to Autoimmune Enteropathy - Halabi, Inbal; Barohom, Marie Noufi; Peleg, Sarit; Trougouboff, Phillippe; Elias-Assad, Ghadir; Agbaria, Rhania; Tenenbaum-Rakover, Yardena (Frontiers in Endocrinology, 2021)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare monogenic disorder, associated with endocrine deficiencies and non-endocrine involvement. Gastrointestinal (GI) manifestations appear in approximately 25% of patients and are the presenting symptom in about 10% of them. Limited awareness among pediatricians of autoimmune enteropathy (AIE) caused by destruction of the gut endocrine cells in APECED patients delays diagnosis and appropriate therapy. We describe an 18-year-old female presenting at the age of 6.10 years with hypoparathyroidism, oral candidiasis and vitiligo. The clinical diagnosis of APECED was confirmed by sequencing the autoimmune regulator-encoding (AIRE) gene. Several characteristics of the disease—Hashimoto's thyroiditis, Addison's disease, diabetes mellitus type 1 and primary ovarian insufficiency—developed over the years. She had recurrent episodes of severe intractable hypocalcemia. Extensive GI investigations for possible malabsorption, including laboratory analyses, imaging and endoscopy with biopsies were unremarkable. Revision of the biopsies and chromogranin A (CgA) immunostaining demonstrated complete loss of enteroendocrine cells in the duodenum and small intestine, confirming the diagnosis of AIE. Management of hypocalcemia was challenging. Only intravenous calcitriol maintained calcium in the normal range. Between hypocalcemic episodes, the proband maintained normal calcium levels, suggesting a fluctuating disease course. Repeated intestinal biopsy revealed positive intestinal CgA immunostaining. The attribution of severe hypocalcemic episodes to AIE emphasizes the need for increased awareness of this unique presentation of APECED. The fluctuating disease course and repeated intestinal biopsy showing positive CgA immunostaining support a reversible effect of GI involvement. CgA immunostaining is indicated in patients with APECED for whom all other investigations have failed to reveal an explanation for the malabsorption.